(3GdGfJbGO Ydi WGFaJi GdTghO hGdYbGOs - (3CMeO Hf YeGO Hf jhSa Hf YHO GdfHj, CHh GdYHGS, TgGH GdOjf GdCbagSj Ke GdbGgQj , GHf GdpYneGO ,J (B808 (3g` s ((3Ydi Hf eMeO Hf YHO Gddg Hf EHQGgje GdTGaYi s)
(3ChdgG (B:s
(3hHYO , adeG cGf GdEfSGf bdjdkG HfaSg , hcKjQkG HCNjg , hcGf jSJhMT ai NdhGJg ESJNQJ Gddg JYGdi ai EjVGM eSGFd eSLdI hQSeJgG HGdEfJbGO s
(3BNQgG (B:s
(3gd cGfJ ai GdEfGA Ch WdYJ ef GdHFQ , aeG GdOdhfLS (B,(3gPG BNQ eG Cda GdTjN GdEeGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs